Intellectual Capital towards Credit Risk Management - Dilemmas - Gwizdała, Jerzy (Kapitał intelektualny a zarządzanie ryzykiem kredytowym - dylematy, 2010)
In the new economic reality, based mainly on integration and globalization of financial markets, banks are forced to seek ways of gaining competitive edge. The management of this capital in a bank is a certain method to succeed in this area. The identification of possible intellectual capital management processes in a bank by defining hidden potential, selection of measurement indicators and methods supporting its utilization and development - all of them are fundamental to achieve established aims. The essential element of intellectual capital in a bank is human capital which has great importance in the credit risk management process.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 138, s. 55-70
Keywords: intellectual capital management; human capital; credit risk management; IC measurenment tools